2022
DOI: 10.3389/fimmu.2022.1033804
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immunogenicity of COVID-19 booster dose vaccination in inflammatory arthritis patients

Abstract: IntroductionPrevious studies have shown a reduction in the effectiveness of primary COVID-19 vaccination in patients with rheumatic diseases. However, limited data is available regarding the effectiveness of the COVID-19 vaccine booster dose, especially on cellular response. The study aimed to assess the humoral and cellular immunogenicity of a booster dose in patients with inflammatory arthritis (IA).Patients and methods49 IA and 47 age and sex-matched healthy controls (HC) were included in a prospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…The waning of humoral immunity after the COVID-19 booster seems to be slower than after the primary vaccination regimen—the levels of responses were higher at T2 than at T0 and none of the IA patients in our study lost the humoral response after more than 6 months from booster vaccination (compared to 20.4% of IA patients after more than 6 months from the primary schedule as reported in our previous study [ 36 ]). We also did not observe any difference in the level of humoral response 6 months after booster vaccination between patients who lost humoral immunity 6 months after primary vaccination and those who maintained it.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The waning of humoral immunity after the COVID-19 booster seems to be slower than after the primary vaccination regimen—the levels of responses were higher at T2 than at T0 and none of the IA patients in our study lost the humoral response after more than 6 months from booster vaccination (compared to 20.4% of IA patients after more than 6 months from the primary schedule as reported in our previous study [ 36 ]). We also did not observe any difference in the level of humoral response 6 months after booster vaccination between patients who lost humoral immunity 6 months after primary vaccination and those who maintained it.…”
Section: Discussionsupporting
confidence: 70%
“…The abrogated immunological response to the primary vaccination schedule results in a faster decline of post-vaccination immunity in IA patients [ 5 , 7 , 16 , 18 , 25 , 26 ], making booster vaccinations among IA patients even more important than in HC. Current studies proved that, though COVID-19 booster vaccinations are effective in IA patients [ 27 , 28 , 29 ], also the immunogenicity of the booster dose is impaired in this group of patients [ 15 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. There are only single studies evaluating the effect of immunomodulatory drugs on the immunogenicity of the booster dose against COVID-19, indicating worsen response after GCs [ 30 ], biological and targeted synthetic disease-modifying antirheumatic drugs (bDMARDs and tsDMARDs) [ 15 , 30 ], and MTX [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…patients (6)(7)(8), also the immunogenicity of the booster dose is impaired in this group of patients (9)(10)(11)(12). In our previous study, we assessed humoral and cellular responses before the booster dose (more than 6 months from the primary vaccination schedule; T0) and 4 weeks after the booster dose (T1) in 49 IA patients and 47 HC vaccinated at the COVID-19 vaccination unit in a rheumatology center (13). Our study showed a boost of humoral and cellular responses in IA patients, but lower than in HC.…”
mentioning
confidence: 99%